2023
DOI: 10.1093/infdis/jiad037
|View full text |Cite
|
Sign up to set email alerts
|

CASP4/11 Contributes to NLRP3 Activation and COVID-19 Exacerbation

Abstract: The SARS-CoV-2 infection triggers activation of the NLRP3 inflammasome, which promotes inflammation and aggravates the severe cases of COVID-19. Here, we reported that SARS-CoV-2 induces upregulation and activation of human Caspase-4/CASP4 (mouse Caspase-11/CASP11), and this process contributes to NLRP3 activation. In vivo infections performed in transgenic hACE2 humanized mice, deficient or sufficient for Casp11, indicate that hACE2 Casp11–/– mice were protected from disease development, with the increased pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
0
3
0
Order By: Relevance
“…For example, while the SCV2 spike and envelope proteins trigger inflammation through the binding of TLR2 and blockade of TLR2 signaling extended survival in mice 83,84 , we demonstrate that TLR2 is required for optimal control of viral replication in the lungs of mice early after infection. Similarly, TNFα, IL-1 and inflammasome pathways have been implicated in the deleterious effects of cytokine storms and cell death later in disease 89,92,[104][105][106] . We found that the pro-inflammatory TNFR1 pathway is critical for early viral control of SCV2 replication in mice and that pulmonary preconditioning with recombinant TNFα potently limits SCV2 viral titers in the lung.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, while the SCV2 spike and envelope proteins trigger inflammation through the binding of TLR2 and blockade of TLR2 signaling extended survival in mice 83,84 , we demonstrate that TLR2 is required for optimal control of viral replication in the lungs of mice early after infection. Similarly, TNFα, IL-1 and inflammasome pathways have been implicated in the deleterious effects of cytokine storms and cell death later in disease 89,92,[104][105][106] . We found that the pro-inflammatory TNFR1 pathway is critical for early viral control of SCV2 replication in mice and that pulmonary preconditioning with recombinant TNFα potently limits SCV2 viral titers in the lung.…”
Section: Discussionmentioning
confidence: 99%
“…. Moreover,105 and is also made available for use under a CC0 license. (which was not certified by peer review) is the author/funder.…”
mentioning
confidence: 99%
“…From day 0 to day 5, mice were evaluated for weight, temperature, and clinical score. The clinical score was measured following the previously described [ 47 ]. At the indicated time point, mice were euthanized, and lungs were collected for following analyses.…”
Section: Methodsmentioning
confidence: 99%